Building conservation capacity in Southeast Asia: Outcomes of the ATBC 2015 Asia-Pacific Chapter meeting conservation education symposium. Issue 3 (3rd July 2017) - Souter, Nicholas J.; Hughes, Alice C.; Savini, Tommaso; Rao, Madhu; Goodale, Eben; Van Nice, Amy; Huang, Natalia; Liu, Jing-Xin; Hunt, Matt P.; O'Connor, David A.; Li Heung-Lam, Anny; Gnuen, Gneb; et al.
ABSTRACT: The "Building Capacity for Conservation in Southeast Asia" symposium was held at the 2015 Association for Tropical Biology and Conservation, Asia-Pacific Chapter meeting. The range of programs discussed fell into three categories: career development, project-specific activities and outreach, and delivering conservation information to diverse audiences. Though different approaches were used, we identified practices and methods which increased the meaning, relevance, and applicability of the messages provided. We found that delivering successful conservation education requires understanding conservation's place in society, developing a feeling of community among students, providing students with financial support, practical teaching, and crafting culturally appropriate messages.